Indonesia dan Dinamika Politik Timur Tengah - Sihbudi, Riza (Jurnal Penelitian Politik, 2011)
The current political tension in Arab states have intensified especially after similar crises that ousted BinAli in Tunisia and Hosni Mubarak in Egypt There are also differences in how nations have responded to each political crisis The Arab regimes are facing strong resistance from the majority of their own people with Libyafalling into civil war Many Libyan people arefed up and disgusted with the leadership of Colonel Qadhafi whohas ruled the countryfor 40 years with desert style authoritarianism People in Libya demanded a succession andpolitical reforms that wouldpave the wayforfreedom ofspeech and association which have eluded the nationforfour decades Then why did the West take a differentpolitical attitude towards thepro democracy movements in theArab countries In the case ofLibya both mass media andpolitical elites drew a line in supporting the resistance movement The Westernforces under NATO even launched military strikes against Libya to support the oppositioncamp as soon as they managed to convince the United Nations to enforce a nofly zone in Libyan airspace Theopportunistic attitude of the West in the case ofLibya is closely related to economic factors which is Libyan oilreserves After successfully controlling Iraq Libya now seems to be the next easyprey especially by hawkish groupsand neo conservative that generally control US oil companies In the case of the NATO s political attitudes towardthe Libyan crisis economic considerations oil are more advanced than political reality Politically Qadhafi is now clearly different from what he was Before 2003 Qadhafi was known as an anti Westfigure The US and itsallies seem reluctant to learnfrom history Theirfailures in Iraq and Afghanistan are not enoughfor them to learnThat s the uglyfact of Western hypocrisy